PRINSIP KHUSUS DAN JENIS LAYANAN PENDIDIKAN BAGI ANAK TUNAGRAHITA DI SLB DHARMA WANITA JIWAN KABUPATEN MADIUN (Eduscotech, 2024)
This study aims to describe the specific educational principles and types of educational services implemented for students with intellectual disabilities at SLB Dharma Wanita Jiwan, Madiun Regency. The research was conducted from September to October 2021 using a qualitative descriptive approach. The participants included the school principal, teachers of mild and moderate intellectual disability classes, and parents of students. Data were collected through observation, in-depth interviews, and documentation, and were analyzed using the Miles and Huberman interactive model, which consists of data reduction, data display, and conclusion drawing. The findings indicate that the educational principles applied at SLB Dharma Wanita Jiwan are based on individualization, functionality, and compassion, whereby each student receives personalized instruction according to their abilities and needs. The school provides various educational services, including adaptive academic instruction, life skills development, therapeutic and counseling services, and socio-emotional guidance. Teachers implement practice-based learning, utilize concrete instructional media, and provide continuous emotional support to students. Supporting factors include teacher competence, effective school leadership, and active parental involvement, while limitations in facilities and the availability of professional therapists remain key challenges. Overall, the implementation of educational principles and services at SLB Dharma Wanita Jiwan is effective in fostering independence and social integration among students with intellectual disabilities.